Sensory Snack Time: A School-Based Intervention Addressing Food Selectivity in Autistic Children - Galpin, James; Osman, Laura; Paramore, Ciara (Frontiers in Education, 2018)
Difficulties with diet and mealtimes, often exacerbated by food selectivity have been highlighted as priority areas of support by parents of autistic children. There is a large body of evidence noting the significant relationship between sensory differences and greater food selectivity in individuals on the autism spectrum. In order to address the needs expressed by parents the present study examined the effect of a whole class, sensory based feeding intervention carried out in a special school setting that was integrated into part of the daily school routine. The intervention sought to become self-sustaining with minimal financial and time costs. In total 23 autistic pupils aged 4-10 took part in the Sensory Snack Time intervention. Results indicated that pupils ate a wider variety of foods and displayed significantly reduced food selectivity, distressed mealtime behaviours and food refusal following the twelve-week intervention. Furthermore, the intervention was successfully integrated into everyday practice and was successfully implemented by existing school staff. Further research is necessary to qualify the precise impact the intervention had on supporting pupils to manage sensory based aversions to foods and to examine the potential for the intervention to be generalised to main meals and different settings, such as pupils’ homes.